Simulation evaluation of a new three-level multiple input, single output DC/DC converter with battery energy storage for DC microgrid applications - Su Su Htet Naing (2019)
Nowadays, DC microgrids have become extremely popular as various renewable resources can be easily connected and intermediate power conversion stages (e.g., AC/DC/AC) can be avoided. Moreover, a lot of home appliances and lighting technologies we use nowadays are native DC loads. These include computers, televisions, and LED light fixtures. Renewable sources, batteries, fuel cells, and electric vehicles are also DC driven [1]. However, due to the nature of power variation in generation from renewable energy sources as well as the consumption, it is very critical to manage the DC grid in such a way that supply meets demand while keeping the DC bus voltage constant. The proposed DC/DC converter in this research helps to fill this gap by having a hybrid energy storage system (HESS) which involves both battery and supercapacitor. The battery and supercapacitor with an interconnection DC/DC converter are used to store and recover the excess energy. The proposed circuit topology presented in this paper is new and superior to most of the existing DC/DC converters for hybrid energy storage system (HESS) with both battery and supercapacitor. The control method, which is known as finite set model predictive current control, is a new application to such a converter. Simulation studies are carried out in MATLAB/Simulink platform. The simulation results are presented and discussed. The results show that the proposed converter meets the objectives by performing well.